Elevated serum leucine levels are associated with cognitive impairment and reduced gray matter and cerebral volume across the Alzheimer's disease continuum - Nasiri, Hamide; Azargoonjahromi, Ali; Nouri, Zahra; Azimi, Sayed Mehrdad; Zand, Hossein; Shourideh, Amir; Mayeli, Mahsa (Pergamon-Elsevier Science Ltd, 2025)
Leucine, a branched-chain amino acid (BCAA), exhibits paradoxical effects in Alzheimer's disease (AD), demonstrating both neuroprotective and neurotoxic roles. While prior studies have investigated leucine's systemic and metabolic impacts, its influence on brain structure remains unexplored. This study aimed to fill this critical gap by examining the relationship between serum leucine levels, brain volume metrics, and cognitive performance in individuals across the AD continuum. Serum leucine concentrations were quantified using the Nightingale Health nuclear magnetic resonance (NMR) platform. Cognitive performance was assessed using the Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog 11 and 13), and structural brain volumes, including total cerebrum, cerebrum gray matter, and total brain gray matter, were derived from T1-weighted magnetic resonance imaging (MRI) via automated segmentation. Mediation analysis was employed to determine whether changes in brain volume mediate the association between serum leucine levels and cognitive performance. Elevated serum leucine levels were significantly associated with reduced total cerebrum volume, cerebrum gray matter volume, and total brain gray matter volume. Furthermore, mediation analysis revealed that these reductions in brain volume partially mediated the relationship between higher leucine levels and poorer cognitive outcomes. These findings provide evidence linking elevated leucine levels to brain atrophy and cognitive decline in AD, suggesting a potentially deleterious role of leucine in neurodegeneration. This highlights the importance of further mechanistic investigations to clarify leucine's role in AD pathology and assess its viability as a therapeutic target.
Keywords: Leucine; Alzheimer disease; Brain atrophy; Cerebrum; Cognitive impairment; Gray matter